EFFECT OF TALENT MANAGEMENT ON THE SUCCESS OF ORGANIZATION DEVELOPMENT - Asrar, Zaeema; Azhar, Tehseen; Hussain, Muddasir (Archives of Business Research, 2018)
This study is done to find the effect of talent management on organization success. The finding of the study is that the effective talent management does result in the success or development of organization. In this study, organization development is divided into two boarder categories, which are positive or negative growth of organization. Positive growth of Organization development was done by recruitment and selection, training and development whereas negative variables are considered employee retention, skill gap and skill shortage. Our study concluded that every employee has some unique talent which differentiates that employee with others which could be resulted in competitive advantage of organization and if that talent would be used for any other position it may cause for discomfort.